Pengembangan Variasi Latihan Lay Up Shoot Bola Basket Pada Siswa Ekstrakurikuler Basket - Rizkei Kurniawan; M Anas Surimeirian; Andi Nova (Universitas Negeri Padang, 2022)
This study aims to determine the development of variations in basketball lay-up exercises for high school basketball extracurricular students in Medan City. This research uses development research (R&D) methods. The research subject is the whole object where there are several resource persons or informants who can provide information about the product variations of lay up exercises in development research. The results of the feasibility test of the variation product by basketball experts obtained a score of 54 with a maximum score of 60 so that the percentage of eligibility is 90%. The results of the feasibility test of the variation product by media experts obtained a score of 94 with a maximum score of 100 so that the percentage obtained was 94%. The results of the trial using the trainer obtained a score of 77 with a maximum score of 80 so that the percentage obtained was 96.25%. The results of the responses of the use trial subjects obtained a score of 2700 with a maximum score of 3000 so that the percentage obtained was 90%. The conclusion of this study is that the development of variations in basketball lay-up exercises for basketball extracurricular athletes at Medan City High School was developed in the form of a guide book. The feasibility of variations in basketball lay-up exercises for basketball extracurricular athletes can be categorized as Very Good, feasible and can be used